Ecocriticism on the Short Stories of Grade 7 Philippine Literature Textbook: Ecological Themes in Teaching - Jezabel Cañales; Jannine Marie B Baldado; Khytz A Agan; Dayanara R Gaan; Genesis Naparan (Journal of Elementary and Secondary School, 2025)
Ecocriticism is the field that is characterized by a lively exchange of opinions, with audiences playing an essential role in the construction of the work of art. This approach challenges readers to reconsider their relationship with the world and their surroundings. This research focuses on examining the relationship between literature and the physical environment in the short stories in the Grade 7 Philippine literature textbook, particularly in the book entitled English Learner Material, with an author and a connection between humans and the physical environment using an ecocritical lens. The ecocritical lens is the literary lens used to examine the different ecological themes in the textbook. The result shows 8 animal themes, 5 pastoral themes, 5 dwelling themes, and 2 apocalypse themes found in the 9 selected short stories from the Grade 7 Philippine literature textbook. Still, not all selected short stories from the Grade 7 textbook exhibit a clear relationship between humans and the physical environment. This study emphasizes the importance of nature in the lives of humans. It raises awareness about the environment and its importance in the Philippine literature textbook used by public schools in the Philippines, particularly in the students' learning and development of the teacher’s pedagogy in teaching literature that will make learning more meaningful and valuable for the students to gain new insights through literature reading. In conclusion, this study fosters environmental awareness among young learners as the stewards of Mother Earth